Evaluation of the Effectiveness of two pesticides Chlorfenapyr and Abamectin on the population density of the stages of the Two spotted spider mites Tetranychus urticae (Koch) (Acari: Tetranychidae) under field conditions. - موسى محمد السويدي طه (Journal of Kerbala for Agricultural Sciences, 2017)
The study aimed to evaluate the Effectiveness of two pesticides Chlorfenapyr and Abamectin on the population density of the stages of the Two spotted spider mites Tetranychus urticae (Koch) (Acari: Tetranychidae) under field conditions and carried out in one area of ​​orchards Al-wond - Hosseinieh city - the holy city of Kerbala .The results showed that two pesticides Chlorfenapyr and Abamectin had an influence evident in the population density of the number of eggs and other stages of mite of the larva and nymph and seriously, as the percentage of the effectiveness of the pesticide Chlorfenapyr are 87 and 100% after 96 and 120 hours of spraying and scored 81.7, 81.1 and 85% after 30.60, 90 days and recorded a percentage of the effectiveness of the pesticide after time, 120 hours of combat morally and clear for the rest of the time difference, where it did not find anyone alive members of the mite factories of this pesticide, and the results achieved by the pesticide Abamectin was 92.2, 100, 82, 79 and 72% after 96 hours, 120 hours, 30 days, 60 days and 90 days, respectively, was not the four directions of the tree and a clear effect on the results of this research at the control Balambadan so we recommend using the pesticide Chlorfenapyr with Abamectin pesticide to control this mite.